Amerika: The Super Bowl and German Imagination. Issue 1 (22nd January 2017) - Dzikus, Lars
Abstract: The Super Bowl has played a central role in the diffusion of American football in Germany, as interviews with the 'founding fathers' of 'gridiron' football clubs and analysis of German media accounts reveal. American football and the Super Bowl have also played an important role in the construction of traditional German Amerikabilder – images, ideas, and symbols associated with America. German media rarely covered American football until the late 1970s. At that time, brief highlight shows of the Super Bowl on German television and broadcasts on the American Forces Network significantly contributed to the diffusion of American football and the emergence of an American football league in Germany in the late 1970s. In the process of covering the Super Bowl, German journalists reproduced Germany's double-headed Amerikabild : America as a model of modernity on the one hand, and as a violent, cultureless society on the other. The press further invoked historical clashes between German Kultur and the dreaded Zivilisation of the West. This exploration of the social processes surrounding the reception of the Super Bowl in Germany employs the theories of cultural globalization, migration, and electronic mediation developed by the anthropologist Arjun Appadurai to explain the complexities of contemporary global cultural flows.